Richard D. Burns and Phillip E. Coyle III: The Challenges of Nuclear Non Proliferation - Ms. Amna Ashraf Khan (CISS Insight Journal, 2017)
Since the end of the Cold War, the omnipresent threat of an allout nuclear war between USA and USSR has receded. Various new apprehensions concerning nuclear weapons have taken its place. The possibility of regional nuclear conflicts in the Korean peninsula; and in the subcontinent of South Asia, and of nuclear proliferation and a subsequent arms race in the conflict prone Middle East, along with the ever increasing threat of nuclear terrorism, form the most recent concerns shaping efforts to strengthen the non-proliferation regime. Spelling out the dominant issues, the book proceeds into a chapter by chapter comprehensive survey of the chronological development of voluntary, bilateral and international non-proliferation initiatives.The opening chapter describes the history of nuclear weapons and the conditions under which the original five nuclear weapon states acquired their nuclear capabilities, and the emergence of the second-tier nuclear weapons states- Israel, India, Pakistan and North Korea- under the motivated impetus of regional security concerns. The book then proceeds to describe the early efforts to curtail the proliferation of nuclear weapons after the discovery of their destructive potential as witnessed by the international community following the Hiroshima and Nagasaki bombings.